Exploring Job Satisfaction of the Faculty at Bulacan Agricultural State College: Input to Enhance Performance in the New Normal - Roselle Urbano; Ma Leonora Sta. Ana; Rhodora Iracta (International Journal of Education, Teaching, and Social Sciences, 2022)
The goal of this study is to find out how satisfied faculty members at Bulacan Agricultural State College are with their jobs. Work environment, rank and employment status, faculty adequacy and loading, pay, fringe benefits and incentives, faculty development, and peer communication are all regarded motivating variables that have an impact on job satisfaction. The survey instrument was completed by 139 faculty members out of a total population of 186, which comprised both permanent and contract-based status academics. It seeks to get insights into the mean job satisfaction ratings of faculty respondents based on a survey. The study showed that the faculty members are generally satisfied with their current circumstances, though the college should consider factors such as training and development that will enable faculty to perform their current jobs effectively and prepare for future assignments, particularly now that the school environment is shifting to a new school environment as the new normal due to the COVID-19 pandemic. The researchers may have concluded that the college should focus more on motivating and maintaining these human resources in order to make them happier and to maximize their efforts by assuring the college's overall greatness.